Pengaruh Serbuk Daun Kelor (Moringa oleifera) Terhadap Apoptosis Sel Hepar Pada Tikus Bunting Diabetes Mellitus - Harry Kurniawan Gondo (Universitas Wijaya Kusuma Surabaya, 2022)
Maternal death rate in Indonesia are still very high. One of the causes is gestasional diabetes mellitus during pregnancy. Some of healing efforts are done, one of them was utilization of plants, in this case, Moringa oleifera. The purpose of this reseach is to know the Moringa oleifera leaf powder on the pregnant wistar rats with gestasional diabetes mellitus. The study design was laboratoric experimental on the wistar rats as the experimental animal, using Control Group Post Test Design on the research. Sample was divided into 2 positive and negative control groups and 4 treatment groups given Moringa oleifera leaf powder that will be induced by alloxan and the liver histopatological result be examined. Total average of liver cell nucleus that goes through apoptosis is lower linear with the increase of the Moringa oleifera leaf powder dose given to the treatment group. After the alloxan induction, the wistar rats’ blood glucose level is increased, caused by the destruction of the beta cell pancreas. There’s a significant difference between the liver cell that go through apoptosis between the four treatment group of wistar rats. The total average of liver cell that go through apoptosis is lower linear with the increase of the Moringa oleifera leaf powder dose given to the treatment group. Oral administration of Moringa leaf powder to white rats with diabetes mellitus was able to improve the histopathological picture of the liver where the brown color was seen to decrease while the methylene green increased. As well as lowering the blood glucose levels of the rats.